458 The effect of cardioversion therapy for atrial fibrillation on AHI in obstructive sleep apnea patients. (3rd May 2021) - Zakhary, Nardine; Mehra, Reena; Monahan, Ken; Sahadevan, Jayakumar; May, Anna
Abstract: Introduction: Sleep apnea (SA) is known to be associated with development of atrial fibrillation (AF), and therapy ameliorates this risk. Case reports and small series raise the possibility of a bidirectional effect of AF on SA burden. We hypothesize that SA control, demonstrated either by residual apnea-hypopnea index (AHI) or pressure during positive airway pressure (PAP) therapy, improves after successful cardioversion. Methods: The cohort included VA patients with SA on PAP therapy who underwent successful outpatient direct-current AF cardioversion. Only patients with good adherence in the peri-procedural period, defined as use most days in the week before and after procedure, were included in the study (n=17). We compared AHI prior to and after cardioversion using the sign test since values were not normally distributed. Since most participants were on auto-titrating PAP, the sign test was also used to compare mean pressure difference in the 7 days before and after the procedure. Results: There was no statistical difference when comparing AHI before and after AF cardioversion therapy (AHI change = -0.45, 95% CI = [-0.94, 0.17]) There was also no difference between mean pressure used for PAP therapy before and after therapy (pressure change = 0.05, 95% CI = [-0.1, 0.33]). Conclusion: This small study did not find an association between successful AF cardioversion and PAP residual AHI or pressure (for auto-titrating machines). A larger cohort may have improved power to detect subtle effects of AF therapy on SA burden. Support (if any): This study was supported by the Career Development Award IK2CX001882 from the United States (U.S.) Department of Veterans Affairs Clinical Sciences Research and Development Service.